The Effect of Presence of Helicobacter pylori on the Severity and Clinical Course of Rosacea - Ninkovic, Djuka J; Gajanin, Vesna; Kutlija, Nevena; Sladojevic, Igor; Krivokuća, Svetozar (Scripta Medica, 2021)
Introduction: Rosacea is manifested by erythema and telangiectasias limited to the regions of cheeks, nose, chin and forehead. Data from the literature indicate a possi- ble causal relationship between Helicobacter pylori infection in the gastrointestinal tract and rosacea, which is confirmed by the improvement of symptoms and clinical picture of rosacea after administered Helicobacter pylori eradication therapy. The aim of the paper was to determine the frequency of Helicobacter pylori infection in patients with rosacea and to examine the effect of the therapy for eradication of infection of this microorganism on the clinical course of rosacea.Methods: Sixty patients with a diagnosis of rosacea who were treated in 2018 at the Clinic for Skin and Venereal Diseases of the University Clinical Centre of Republic of Srpska were analysed. Patients were examined during their visit to a dermatologist (first week) and after applied therapy (sixth week). Subjects were divided into two groups - group I consisted of subjects in which, in addition to rosacea, the presence of Helicobacter pylori was registered and for whom the topical therapy and triple therapy for eradication of Helicobacter pylori were administered, and group II, which included subjects in which, in addition to rosacea, the presence of Helicobacter pylori was not registered and for whom only topical therapy was administered. Statistical processing was performed in the IBM SPSS Statistics 21 software package.Results: Helicobacter pylori infection was registered in 45 % of patients. Statistical significance was determined between the presence of Helicobacter pylori infection and the presence of pustules in patients with rosacea (p = 0.027), with an occurrence of pustules significantly more frequent in patients belonging to group I (55.6 %) than in patients belonging to group II (24.2 %).Conclusion: Therapy for eradicating Helicobacter pylori infection improves the clini- cal course of rosacea, especially in the stage of papules and pustules.
Keywords: Rosacea; Helicobacter pylori; drug effects